2020
DOI: 10.1007/s11357-020-00177-1
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing identifies senescent cerebromicrovascular endothelial cells in the aged mouse brain

Abstract: Age-related phenotypic changes of cerebromicrovascular endothelial cells lead to dysregulation of cerebral blood flow and blood-brain barrier disruption, promoting the pathogenesis of vascular cognitive impairment (VCI). In recent years, endothelial cell senescence has emerged as a potential mechanism contributing to microvascular pathologies opening the avenue to the therapeutic exploitation of senolytic drugs in preclinical studies. However, difficulties with the detection of senescent endothelial cells in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(135 citation statements)
references
References 115 publications
3
113
0
Order By: Relevance
“…The top contributors to the first principal component (PC1), defined as those with more than one standard deviation above the mean contribution, included senescence-associated genes (IL6, CXCL8, CSF2) and cell adhesion genes (SELE and MAdCAM-1) ( Figure 5A ). As these genes are associated with endothelial dysfunction and/or senescence ( 23 , 24 , 31 , 71 73 ), we hypothesized that PC-derived composite gene expression scores (a.k.a. PC composite score) would distinguish B3 from B1 microvessels.…”
Section: Resultsmentioning
confidence: 99%
“…The top contributors to the first principal component (PC1), defined as those with more than one standard deviation above the mean contribution, included senescence-associated genes (IL6, CXCL8, CSF2) and cell adhesion genes (SELE and MAdCAM-1) ( Figure 5A ). As these genes are associated with endothelial dysfunction and/or senescence ( 23 , 24 , 31 , 71 73 ), we hypothesized that PC-derived composite gene expression scores (a.k.a. PC composite score) would distinguish B3 from B1 microvessels.…”
Section: Resultsmentioning
confidence: 99%
“…Cellular senescence includes a senescence-associated secretory phenotype and biomarkers such as beta galactosidase and p16 Ink4A . Recent transcriptomic studies have observed age-associated increases in the number of BECs that exhibit high levels of senescence-related gene expression 15 . One regulator of senescence that mediates vBBB dysfunction is sirtuin-1; the loss of sirtuin-1 with aging is associated with vBBB dysfunction 16 .…”
Section: The Bbb and Models Of Agingmentioning
confidence: 99%
“…setup: 10X Genomics Chromium, Illumina NextSeq500 Remarks: Senescence pathway activation was found in a cluster of endothelial cells. Aging Cerebromicrovascular Atlas ( Kiss et al, 2020 ) Tissues: brain Animals/Cells: ∼9000 cells from 6 male C57BL/6 mice, 3 mo and 28 mo Heterogeneity: Not investigated Exp. setup: 10X Genomics Chromium; Illumina NovaSeq 6000 Remarks: ∼10 % of cells display cellular senescence, based on a precompiled list of markers.…”
Section: Single-cell Analyses Of Aging and Senescencementioning
confidence: 99%
“…Further studies up to now focused on the blood ( Elyahu et al, 2019 ; Grover et al, 2016 ; Martinez-Jimenez et al, 2017 ), the pancreas ( Elyada et al, 2019 ; Enge et al, 2017 ; Thompson et al, 2019 ), the brain ( Hammond et al, 2019 ; Kiss et al, 2020 ; Ximerakis et al, 2019 ) and the lung ( Angelidis et al, 2019 ; Reyfman et al, 2019 ), see Table 1 and the next sections. Of note, comparing data of the Tabula Muris Senis and some of the single-tissue studies, we note high consistency among studies when looking at aging/senescence-related markers, see Box 2.…”
Section: Single-cell Analyses Of Aging and Senescencementioning
confidence: 99%
See 1 more Smart Citation